Amino-functionalized ionic liquid / boron-doped glass microsphere composite electrode for detecting acetaminophen, preparation method and application thereof
Patent Information
- Application Number
- CN202410090064.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-01-23
AI Technical Summary
[0003]基于此,本发明提供一种用于检测对乙酰氨基酚的氨基功能化离子液体/玻碳微球复合物电极,以解决现有技术中存在的电极的重现性较差,且电极再生过程复杂的技术问题
[0026]本发明提供了一种用于检测对乙酰氨基酚的氨基功能化离子液体/玻碳微球复合物电极,具有良好的重现性和稳定性,在最优的实验条件下,利用方波伏安法定量检测,对同一份对乙酰氨基酚电解液,使用同一支电极进行6次平行测定,通过DPV图中的曲线读出峰电流,计算得到相对标准偏差(RSD)为1.04%;同时,分别使用6支电极检测对乙酰氨基酚电解液,通过DPV曲线获得的峰电流值计算得到其相对标准偏差为2.89%,这说明该电极具有出色的重现性。将电极室温保存1个月后,对乙酰氨基酚的峰电流值为初始值的92.26%,说明该电极具有良好的稳定性。
Smart Images

Figure CN118010821B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical analysis methods, specifically relating to an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, its preparation method, and its application. Background Technology
[0002] Acetaminophen, commonly known as paracetamol, is a common acetanilide antipyretic and analgesic widely used in clinical practice. Acetaminophen has certain toxic side effects on the human body; overdose can lead to liver necrosis. Therefore, its dosage is strictly controlled, making the determination of acetaminophen of significant practical importance. Currently, many feasible techniques exist for the detection of acetaminophen, such as chromatography, spectrophotometry, and electrochemical methods. Electrochemical analysis and detection techniques have enormous development potential in modern detection technology due to their ease of operation, high sensitivity and accuracy, ease of miniaturization, and ability to achieve online monitoring. The key to the performance of electrochemical sensors lies in the construction of functionally modified electrodes. Therefore, researchers are dedicated to studying and developing composite materials with different functions to construct high-performance electrochemical sensors. In the prior art, Chinese invention patent application number CN202010357494.4 discloses a carbon nanotube-modified electrode for acetaminophen detection and its preparation method, including S1, preparing a carbon nanotube modifier; S2, after pretreating the electrode, applying the carbon nanotube modifier to its surface using a micro-syringe, and drying at room temperature to obtain the carbon nanotube-modified electrode; wherein the preparation method of the carbon nanotube modifier is: dispersing multi-walled carbon nanotubes in a 0.5% Nafion solution to obtain a 1 mg / mL carbon nanotube modifier. The carbon nanotube-modified electrode prepared by this invention was tested 6 times with the same solution. After each test, the electrode was regenerated by circulating the base solution for 6 cycles. The calculated relative standard deviation (RSD) was 2.9%. The reproducibility of the above electrode is poor, and the electrode regeneration process is complex. Summary of the Invention
[0003] Based on this, the present invention provides an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, in order to solve the technical problems of poor reproducibility and complex electrode regeneration process in the prior art.
[0004] The present invention also provides a method for preparing the above-mentioned amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, which is simple in steps and easy to operate.
[0005] This invention also provides a method for detecting acetaminophen, based on the aforementioned amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen. This method exhibits good reproducibility and stability. Under optimal experimental conditions, quantitative detection was performed using square wave voltammetry. Six parallel measurements were conducted on the same acetaminophen electrolyte using the same electrode. The peak current was read from the DPV curve, and the calculated relative standard deviation (RSD) was 1.04%. Simultaneously, the acetaminophen electrolyte was detected using six different electrodes, and the calculated RSD of the peak current values obtained from the DPV curves was 2.89%, indicating excellent reproducibility of the electrode. After storing the electrode at room temperature for one month, the peak current value of acetaminophen remained at 92.26% of the initial value, demonstrating the good stability of the electrode.
[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:
[0007] A method for preparing an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen includes:
[0008] S10. Mix and grind the nano-graphite powder, glassy carbon microspheres, amino-functionalized ionic liquid and paraffin oil thoroughly to obtain a paste.
[0009] S20. Fill the container with the paste and shape it to obtain an electrode post;
[0010] S30. Polish the surface of the electrode post to obtain an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen.
[0011] The amino-functionalized ionic liquid is 1-aminopropyl-3-methylimidazolium hexafluorophosphate ionic liquid.
[0012] Preferably, in the above-described method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, the volume ratio of the amino-functionalized ionic liquid to paraffin oil is 1:1.
[0013] Preferably, in the above-described method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, the mass ratio of the nano-graphite powder to the amino-functionalized ionic liquid is 3:1.5.
[0014] Preferably, in the above-described method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, the mass ratio of the nano-graphite powder to the glassy carbon microspheres is 3:2.
[0015] Preferably, in the above-described method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, the content of the glassy carbon microspheres is 20-60 wt%.
[0016] An amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen is prepared using the above-described preparation method for an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen.
[0017] An electrochemical sensor for detecting acetaminophen uses the aforementioned amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen as the working electrode.
[0018] A method for detecting acetaminophen includes the following steps:
[0019] T10. Construct the electrochemical sensor described above for detecting acetaminophen;
[0020] T20. Construct an electrolyte system, which consists of the sample to be tested and PBS buffer solution;
[0021] T30, Detect the concentration of acetaminophen.
[0022] Preferably, in the above-mentioned method for detecting acetaminophen, the concentration of the PBS buffer solution is 0.1 mol / L and the pH value is 5-7.
[0023] Preferably, in the above-described method for detecting acetaminophen, the detection of the concentration of acetaminophen includes the following steps:
[0024] At room temperature, using the square wave voltammetry method, enrichment was achieved at an open circuit potential for 60-150 seconds.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] This invention provides an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, exhibiting good reproducibility and stability. Under optimal experimental conditions, quantitative detection was performed using square wave voltammetry. Six parallel measurements were conducted on the same acetaminophen electrolyte using the same electrode, and the peak current was read from the DPV curve, yielding a relative standard deviation (RSD) of 1.04%. Simultaneously, using six different electrodes to detect acetaminophen electrolytes, the peak current values obtained from the DPV curves showed a relative standard deviation of 2.89%, indicating excellent reproducibility. After storing the electrode at room temperature for one month, the peak current value for acetaminophen remained at 92.26% of the initial value, demonstrating the electrode's good stability.
[0027] This invention also provides a method for preparing an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen. The method involves simply mixing and grinding nano-graphite powder, glassy carbon microspheres, amino-functionalized ionic liquid, and binder to obtain a paste; then filling the paste into a container, shaping it to obtain an electrode column, and polishing the surface smooth. This method is simple, easy to operate, and the surface can be easily renewed; a new electrode surface can be obtained with simple polishing.
[0028] The present invention also provides a method for detecting acetaminophen, based on the above-mentioned amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, which not only has good sensitivity and a wide detection range, but also has good reproducibility and stability. Attached Figure Description
[0029] Figure 1 Cyclic voltammetry for different electrodes (a) nano-CPE, (b) GCPE, and (c) NH2-IL-GCPE in a 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution containing 0.1 M KCl, scan rate: 50 mV s -1 .
[0030] Figure 2 The figures show cyclic voltammograms of three electrodes at different scan rates in a mixed probe solution, where (a) nano-CPE; (b) GCPE; and (c) NH2-IL-GCPE are in a solution containing 0.1 M KCl in 5 mM [Fe(CN)6]. 3- / 4- Cyclic voltammograms in solution at different scan rates, from the inside out: 25, 50, 75, 100, 125, 150, 175, 200 mV s -1 .
[0031] Figure 3 Differential pulse voltammetry of 50 μM acetaminophen on (a) nano-CPE; (b) GCPE; (c) NH2-IL-GCPE.
[0032] Figure 4 The figures show cyclic voltammetry of acetaminophen at different scan rates. (A) shows cyclic voltammetry of 50 μM acetaminophen on NH₂-IL-GCPE at different scan rates, from bottom to top: 25, 50, 75, 100, 125 mV s. -1 (B) Linear relationship between anode peak current and sweep rate.
[0033] Figure 5The effects of 0.1M PBS at different pH values on the peak potential and peak current of acetaminophen on NH2-IL-GCPE were investigated. (A) Differential pulse voltammograms of 50 μM acetaminophen at different pH values (pH: ae = 4, 5, 6, 7, 8); (B) Effect of pH value on the peak potential and peak current of acetaminophen.
[0034] Figure 6 The effect of glassy carbon microsphere content on the response current of 50 μM acetaminophen.
[0035] Figure 7 The effect of open circuit potential and different enrichment potentials on the response current of 50 μM acetaminophen.
[0036] Figure 8 To investigate the effect of enrichment time on the response current of 50 μM acetaminophen.
[0037] Figure 9 Differential pulse voltammetry plots of acetaminophen at different concentrations on NH2-IL-GCPE (concentrations from bottom to top are: 0, 1, 5, 10, 20, 50, 100, 150, 200, 250, 300 μM acetaminophen; inset plots are differential pulse voltammetry plots of 0.2 and 0.5 μM acetaminophen; (B) Linear relationship between acetaminophen peak current and concentration. Detailed Implementation
[0038] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other. The technical solutions of the present invention will be further described below with reference to the accompanying drawings of the embodiments of the present invention. The present invention is not limited to the following specific embodiments.
[0039] It should be understood that the same or similar reference numerals in the accompanying drawings of the embodiments correspond to the same or similar components. In the description of this invention, it should be understood that if terms such as "upper," "lower," "front," "rear," "left," "right," "top," and "bottom" indicate orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, they are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or component referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms describing positional relationships in the accompanying drawings are for illustrative purposes only and should not be construed as limiting this patent. Those skilled in the art can understand the specific meaning of the above terms according to the specific circumstances.
[0040] In one specific embodiment, a method for preparing an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen includes the following steps:
[0041] S10. Mix and grind the nano-graphite powder, glassy carbon microspheres, amino-functionalized ionic liquid and paraffin oil thoroughly to obtain a paste.
[0042] Nano-graphite powder, glassy carbon microspheres, and amino-functionalized ionic liquid were weighed separately, added to paraffin oil, and then mixed and ground evenly in an agate mortar to obtain a paste. The amino-functionalized ionic liquid was 1-aminopropyl-3-methylimidazolium hexafluorophosphate ionic liquid.
[0043] Nano-graphite powder has a large specific surface area and high unit volume density, allowing it to contact more analytes per unit area as a substrate electrode material, making it more sensitive to changes in current. Nano-graphite powder exhibits superior adsorption, wear resistance, lubricity, and magnetism compared to ordinary graphite powder, broadening its application fields, such as solid lubricants for ships, locomotives, and motorcycles, conductive materials, and refractory materials. Glassy carbon microspheres are a high-performance electrode material with a unique three-dimensional nanostructure. Due to their excellent conductivity, high specific surface area, open pore structure, and ease of cation modification, they have been widely used in various fields of electrochemical analysis. Ionic liquids are special organic compounds composed only of specific anions and cations, existing as liquids at room temperature. They are known as green solvents due to their stability, non-volatility, non-flammability, and recyclability. The structural characteristics of ionic liquids allow for the modification of their properties to a certain extent, enabling the combination of ions to meet the specific physical and chemical properties required for each application, such as melting point, dielectric constant, viscosity, polarity, and water solubility. Functionalized ionic liquids (TSILs) introduce specific functional groups onto anions or cations, giving them unique physical and chemical properties to meet specific needs. The amino-functionalized ionic liquid in this scheme is 1-aminopropyl-3-methylimidazolium hexafluorophosphate, CAS number: 914770-48-2, molecular weight: 285.17, molecular formula: C7H 14 F6N3P. This method combines amino-functionalized ionic liquids with glassy carbon microspheres, which can fill the gaps between the microspheres in the carbon paste, making the microspheres more tightly connected. This effectively increases the effective surface area of the electrode, promotes electron transfer, increases peak current, and thus improves sensor performance. Simultaneously, the higher viscosity of the amino-functionalized ionic liquid allows for tighter bonding of the nano-graphite powder, further increasing the peak current.
[0044] Preferably, the volume ratio of the amino-functionalized ionic liquid to the paraffin oil is 1:1.
[0045] Preferably, the mass ratio of the nano-graphite powder to the amino-functionalized ionic liquid is 3:1.5.
[0046] Preferably, the mass ratio of the nano-graphite powder to the glassy carbon microspheres is 3:2.
[0047] Preferably, the content of the glassy carbon microspheres is 20–60 wt%. Experiments have shown that when the content of glassy carbon microspheres is between 0 and 40%, the peak current increases with increasing glassy carbon microsphere content, reaching its maximum at 40%. However, when the glassy carbon microsphere content exceeds 40%, the peak current decreases with increasing glassy carbon microsphere content. This indicates that an appropriate amount of glassy carbon microspheres can effectively increase the specific surface area of the modified electrode, which is beneficial for the adsorption of the analyte and increases the enrichment of the target analyte on the modified electrode. However, if the glassy carbon microsphere content exceeds a certain range, it will increase the background current of the modified electrode, affecting the response value of acetaminophen. Therefore, the optimal content of glassy carbon microspheres constituting the modified electrode is 40%.
[0048] S20. The paste is filled into a container and shaped to obtain an electrode post.
[0049] The prepared paste is placed in a polytetrafluoroethylene tube or glass tube and pressed to fix it, thus obtaining an electrode column.
[0050] S30. The surface of the electrode post is polished to obtain an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen.
[0051] The electrode surface is polished smooth on weighing paper, and the prepared electrode is called an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode (NH2-IL-GCPE).
[0052] In another embodiment of the present invention, an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen is prepared using the above-described preparation method for an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen.
[0053] In another embodiment of the present invention, an electrochemical sensor for detecting acetaminophen uses the above-mentioned amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen as the working electrode.
[0054] In another embodiment of the present invention, a method for detecting acetaminophen includes the following steps:
[0055] T10. Construct the electrochemical sensor described above for detecting acetaminophen.
[0056] For example, an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, prepared as described above, can be used as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum wire electrode as the auxiliary electrode.
[0057] T10. Construct an electrolyte system, which consists of the sample to be tested and PBS buffer solution.
[0058] Preferably, a PBS buffer solution with a concentration of 0.1 mol / L and a pH value of 5-7 is selected as the main electrolyte of the electrolyte system. Then, an appropriate amount of the sample to be tested containing acetaminophen is added to the PBS buffer solution to obtain the electrolyte system.
[0059] T10, Detect the concentration of acetaminophen.
[0060] Furthermore, the detection of acetaminophen concentration includes the following steps: enriching at an open circuit potential for 60s-150s using square wave voltammetry at room temperature.
[0061] For example, based on the electrochemical sensor and the electrolyte system, at room temperature, using square wave voltammetry, the open circuit potential is enriched for 60s to 150s, and then tested using differential pulse voltammetry. The corresponding curves (DPVs) are recorded, and the changes in peak current and peak potential are analyzed to directly or indirectly obtain the concentration of acetaminophen.
[0062] The following specific experimental process further illustrates the technical solution and technical effects of the present invention.
[0063] 1. Main reagents and experimental instruments
[0064] 1.1 Main Reagents: Acetaminophen (Shanghai Aladdin Chemical Reagent Co., Ltd.); 1-Aminopropyl-3-methylimidazolium hexafluorophosphate (Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences); glassy carbon microspheres (Sigma-Aldrich); nano-graphite powder (Xianfeng Nanotechnology Co., Ltd.); paraffin oil (Sigma-Aldrich); the following reagents were purchased from Sinopharm Group Co., Ltd.: disodium hydrogen phosphate, potassium dihydrogen phosphate, potassium ferrocyanide, potassium chloride, potassium ferrocyanide; ultrapure water was prepared in the laboratory. All reagents in this experiment were of analytical grade and did not require purification before use.
[0065] 1.2 Experimental Apparatus
[0066] Please refer to Table 1 for the main experimental instruments:
[0067] Table 1. Models and Manufacturers of Experimental Instruments
[0068]
[0069] 2. Electrode Preparation
[0070] 0.03 g of nano-graphite powder, 0.02 g of glassy carbon microspheres, and 10 μL of amino-functionalized ionic liquid were weighed using an electronic balance. 10 μL of paraffin oil was added, and the mixture was then ground evenly in an agate mortar. The prepared mixture was placed in an electrode tube with a diameter of 3 mm and pressed to fix it in place. The electrode surface was then polished smooth on weighing paper. The prepared electrode is called the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode (NH2-IL-GCPE).
[0071] In contrast, a glassy carbon microsphere paste electrode (GCPE) was prepared using the same method. This electrode was made by weighing 0.02 g of glassy carbon microspheres, 0.03 g of nano-graphite powder, and 20 μL of paraffin oil and mixing them evenly in an agate mortar. A nano carbon paste electrode (nano-CPE) was also prepared by weighing 0.05 g of nano-graphite powder and 20 μL of paraffin oil and grinding them together.
[0072] 3. Analytical Methods
[0073] A three-electrode system was employed: the working electrode was an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode, the reference electrode was a saturated calomel electrode, and the auxiliary electrode was a platinum wire electrode. The modified electrode was tested using differential pulse voltammetry in 0.1 M phosphate buffered saline (PBS) containing acetaminophen at a pH 6.0, with an enrichment potential of 0.2 V and an enrichment time of 90 s. The corresponding curves (DPVs) were recorded, and the changes in peak current and peak potential were analyzed.
[0074] 4. Electrochemical characterization of modified electrodes
[0075] To investigate the electrochemical performance of the electrochemical sensor, cyclic voltammetry (CV) was used to electrochemically characterize three different electrodes. Figure 1 The figures show the cyclic voltammetry of different electrodes—nano-CPE, GCPE, and NH2-IL-GCPE—in a 5 mM K3[Fe(CN)6] / K4[Fe(CN)6] solution containing 0.1 M KCl. The figures show a pair of relatively small redox peaks on the nano-CPE curve (curve a). Compared to nano-CPE, the redox peak current on the GCPE curve (curve b) is increased, indicating that the glassy carbon microspheres can improve the surface microstructure of the modified electrode, providing more active sites for the substrate. On the NH2-IL-GCPE curve (curve c), the redox peak current is significantly increased, exhibiting the largest relative current response. Simultaneously, its redox peak potential difference (ΔEp) is significantly reduced, indicating that the amino-functionalized ionic liquid / glassy carbon microsphere composite can effectively improve the electrochemical performance of the modified electrode, promote the electron transfer rate between the substrate and the modified electrode, and thus amplify the signal.
[0076] 5. Surface area study
[0077] To further investigate the modified electrodes, we estimated the effective surface area of different electrodes. Figure 2 Cyclic voltammograms of three electrodes at different scan rates in a mixed probe solution are shown. Based on the measurement data, in nano-CPE ( Figure 2 A) GCPE ( Figure 2 B) and NH2-IL-GCPE ( Figure 2 C) Peak current at the upper anode (Ipa) and the square root of the sweep rate (υ) 1 / 2 All of them exhibit a good linear relationship, and their linear equations are as follows:
[0078] nano-CPE: I(μA)=185.1134v 1 / 2 (V 1 / 2 s -1 / 2 )+30.6121(r 2 =0.9975);
[0079] GCPE: I(μA)=214.5414v 1 / 2 (V 1 / 2 s -1 / 2 )+54.2502(r 2 =0.9937);
[0080] NH2-IL-GCPE: I(μA)=601.0780v 1 / 2 (V 1 / 2 s -1 / 2 -1.3824(r) 2 =0.9940);
[0081] For reversible reactions, the peak current varies with the square root of the scan rate according to the Randles-Sevcik equation:
[0082] Ipa=(2.69×10 5 )n 3 / 2 AC0D R 1 / 2 υ 1 / 2 (1)
[0083] Where Ipa is the anode peak current, n is the number of electrons transferred, A is the effective surface area of the electrode, and C0 is [Fe(CN)6]. 3- / 4- The concentration of D R Let be the diffusion coefficient, and υ be the scan rate. For 5 mM [Fe(CN)6] containing 0.1 M KCl... 3- / 4- Solution, n=1, D R =6.30×10 -6 cm 2 s-1
[28] According to Ipa and υ 1 / 2 From the slope of the relationship, the active surface areas of nano-CPE, GCPE, and NH2-IL-GCPE can be calculated to be 0.055, 0.064, and 0.178 cm², respectively. 2 The results show that the amino-functionalized ionic liquid / glassy carbon microsphere composite significantly improves the performance of the modified electrode, with a significantly increased effective surface area compared to other electrodes. Therefore, the surface microstructure of NH2-IL-GCPE provides more binding sites for analytes, thereby amplifying the response signal.
[0084] 6. Electrochemical behavior of acetaminophen
[0085] Figure 3 Differential pulse voltammetry of 50 μM acetaminophen on nano-CPE, GCPE, and NH2-IL-GCPE. Figure 3 As can be seen, a small oxidation peak of acetaminophen can be observed on nano-CPE (curve a), with a peak current of only 1.496 μA. However, after modification with an appropriate amount of glassy carbon microspheres, the peak current on GCPE (curve b) increases to 2.063 μA. This is because the glassy carbon microspheres have a larger specific surface area, thereby increasing the effective surface area of the modified electrode, increasing the enrichment of acetaminophen on the modified electrode surface, and thus increasing the response current. As shown in curve c, the peak current of acetaminophen on NH2-IL-GCPE is significantly increased (16.83 μA), approximately eight times that of the peak current of acetaminophen on GCPE. This is because the amino-functionalized ionic liquid can effectively bind with the glassy carbon microspheres, filling the gaps between the glassy carbon microspheres, significantly enhancing the conductivity of the modified electrode, and promoting the electron transfer rate of acetaminophen. Meanwhile, compared with nano-CPE and GCPE, the peak potential of acetaminophen on NH2-IL-GCPE is significantly negatively shifted, indicating that NH2-IL-GCPE exhibits better electrocatalytic activity for acetaminophen.
[0086] 7. Effect of sweep speed
[0087] Figure 4 This is a cyclic voltammogram of acetaminophen at different scan rates. (25–125 mV s) -1 Within the scan rate range, the oxidation peak current of acetaminophen gradually increases with increasing scan rate, while its oxidation peak potential also shifts positively with increasing scan rate. The results indicate that the oxidation peak current of acetaminophen is directly proportional to the scan rate, with the linear equation: I(μA)=0.2447υ(mV s) -1 )+0.5729(r 2=0.9848), which indicates that the reaction of acetaminophen on NH2-IL-GCPE is an adsorption-controlled electrochemical reaction process.
[0088] 8. Effects of different pH values
[0089] Figure 5 The effect of 0.1M PBS at different pH values on the peak potential and peak current of acetaminophen on NH2-IL-GCPE. Figure 5 A is the differential pulse voltammogram of 50 μM acetaminophen in 0.1 M PBS at different pH values. Figure 5 Figure B illustrates the changes in peak potential and peak current of acetaminophen caused by solutions at different pH values. As shown in the figure, the peak current of acetaminophen gradually increases as the pH value changes from 4 to 6, reaching its maximum at pH = 6. When the pH value is greater than 6, the peak current of acetaminophen shows a decreasing trend. Simultaneously, as the pH value changes from 4 to 8, the peak potential of acetaminophen shifts negatively, and the relationship between peak potential (E) and pH value is linear, with the linear equation: E(V) = -0.0571pH + 0.7517(r) 2 =0.9962). The slope of the equation is 57.1 mV pH. -1 pH value 59.0 mV (contrary to the theoretical value) -1 The fact that they are very close indicates that the number of protons and electrons participating in the electrode reaction are equal.
[0090] 9. Effect of Modifier Content
[0091] The effects of different ratios of carbon nanoparticles and glassy carbon microspheres on the response current of acetaminophen were investigated. Figure 6 As shown, when the content of glassy carbon microspheres is between 0% and 40%, the peak current increases with increasing glassy carbon microsphere content, reaching its maximum at 40%. However, when the glassy carbon microsphere content exceeds 40%, the peak current decreases with further increases in glassy carbon microsphere content. This indicates that an appropriate amount of glassy carbon microspheres can effectively increase the specific surface area of the modified electrode, which is beneficial for the adsorption of the analyte and increases the enrichment of the target analyte on the modified electrode. However, if the glassy carbon microsphere content exceeds a certain range, it will increase the background current of the modified electrode, affecting the response value of acetaminophen. Therefore, the optimal content of glassy carbon microspheres constituting the modified electrode is 40%.
[0092] 10. The effect of enrichment potential
[0093] Figure 7The effects of open-circuit potential and different enrichment potentials on the response current of 50 μM acetaminophen were discussed. As shown in the figure, when the applied potential is between -0.2 V and 0.4 V, the peak current of acetaminophen on the modified electrode first increases and then decreases. The peak current reaches its maximum at an applied potential of 0.2 V. The variation of the peak current of acetaminophen at the open-circuit potential was also investigated. The results showed that acetaminophen also had a good response value at the open-circuit potential, but a higher current response was obtained when detected at an enrichment potential of 0.2 V. This may be because a suitable enrichment potential is more conducive to the enrichment of acetaminophen on the modified electrode and can accelerate electron transfer between the substrate and the electrode surface. Therefore, an applied potential of 0.2 V was selected as the optimal enrichment potential.
[0094] 11. The effect of enrichment time
[0095] Figure 8 To investigate the effect of enrichment time on the response current of 50 μM acetaminophen, previous studies have shown that the electrochemical reaction of acetaminophen on NH₂-IL-GCPE is adsorption-controlled, indicating that enrichment time has a significant impact on the magnitude of the response current. As shown in the figure, as the enrichment time increases from 10 s to 90 s, the adsorption amount of acetaminophen on the modified electrode also increases, and the corresponding peak current increases. However, when the enrichment time exceeds 90 s, the peak current no longer increases, indicating that the adsorption amount of acetaminophen on the modified electrode reaches saturation. Considering both detection sensitivity and analytical efficiency, an enrichment time of 90 s was selected as the optimal enrichment time.
[0096] 12. Standard Curve
[0097] Differential pulse voltammetry was used to detect a series of concentrations of acetaminophen standard solutions under optimal experimental conditions. The results are as follows: Figure 9 As shown. In 2×10 -7 ~2×10 -4 mol L -1 Within the specified concentration range, the peak current of acetaminophen increases linearly with increasing concentration. The linear equation and detection limit are as follows: I(μA) = 0.3261c(μM) + 0.6071(r). 2 =0.9941) and 5×10 -8 mol L -1 When the concentration of acetaminophen is >2.5 × 10⁻⁶ -4 mol L -1At that time, its response current no longer increases linearly. In Table 2, by comparing with other sensors, we found that the electrochemical sensor constructed in this paper exhibits better electrochemical performance, with high sensitivity to acetaminophen, mainly reflected in a comparable or wider linear range and a lower detection limit.
[0098] Table 2 Comparison of acetaminophen detection using different modified electrodes
[0099]
[0100] a MCPE: Modified carbon paste electrode; b PR: Barton and Reid reagents; c CS: Chitosan; d Ag-Pd: Silver-Palladium Bimetallic Nanoparticles; e rGO: Reduced graphene oxide; f GCE: Glassy carbon electrode; g NiO-CuO: Nickel oxide and copper oxide nanoparticles; h GR: Graphene; i CoO x Cobalt oxide; j CCE: Carbon ceramic electrode.
[0101] 13. Reproducibility and Stability
[0102] In a 0.1M pH 6.0 PBS solution containing 50 μM acetaminophen, six parallel measurements were performed using the same NH2-IL-GCPE modified electrode. The peak current was read from the DPV curve, and the calculated relative standard deviation (RSD) was 1.04%. Simultaneously, six separate NH2-IL-GCPE modified electrodes were used to detect 50 μM acetaminophen, and the RSD of the peak current values obtained from the DPV curves was 2.89%, indicating that the electrode has excellent reproducibility. After storing the modified electrode at room temperature for one month, the peak current of acetaminophen was 92.26% of the initial value, indicating that NH2-IL-GCPE has good stability.
[0103] 14. Interference Research
[0104] To investigate the anti-interference ability of the NH2-IL-GCPE modified electrode, organic compounds and inorganic ions that might be present during the detection process were added to 0.1M pH 6.0 PBS solution, and DPV tests were performed to observe the current changes of the acetaminophen peak. The results showed that 500 times the K... + Na + Cl -200 times the amount of glucose (Glu), ascorbic acid (AA), and 100 times the amount of iron. 2+ Cu 2+ SO4 2- NO3 - 10 times the amount of adrenaline (EP) and the same amount of dopamine (DA) and uric acid (UA) to 2×10 - 5 mol L -1 The detection of acetaminophen was not significantly affected, indicating that the NH2-IL-GCPE modified electrode has good selectivity for acetaminophen.
[0105] 15. Actual Sample Detection and Recovery Experiment
[0106] To verify the ability of NH2-IL-GCPE to detect real samples, this paper selected compound acetaminophen tablets (Taiji Group) and 999 Cold Relief Granules (Sanjiu Group) as analytes to detect the content of acetaminophen in the drugs. Before detection, the real samples underwent simple pretreatment. One compound acetaminophen tablet was ground into powder in a mortar, a certain amount of powder was weighed into a volumetric flask, and the volume was adjusted to 10 mL with 50% methanol. After dissolution, the sample was centrifuged, and the supernatant was collected for later use. A certain amount of Cold Relief Granules was dissolved in ultrapure water under heating conditions and the volume was adjusted to 10 mL for later use. Under optimal conditions, the spiked recovery method was used for the experiment. The results are shown in Table 3. The recovery rate in the compound acetaminophen tablet sample was 101.8%, with a relative standard deviation of 2.91%; the recovery rate in the Cold Relief Granules sample was 99.7%, with a relative standard deviation of 3.49%. The results indicate that the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode NH2-IL-GCPE can detect real samples.
[0107] Table 3. Detection results of acetaminophen concentration in samples by NH2-IL-GCPE (n=3)
[0108]
[0109] This application describes the construction of an electrochemical sensor for acetaminophen based on an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode (NH2-IL-GCPE). The electrochemical characteristics of the modified electrode were investigated, and the effects of detection conditions on the acetaminophen peak current were discussed. Compared with nano-CPE and GCPE electrodes, NH2-IL-GCPE exhibits a larger active surface area and higher electrocatalytic activity for acetaminophen. Results show that the highest response current for acetaminophen is obtained in 0.1 M phosphate buffer (pH 6.0) at an enrichment potential of 0.2 V and an enrichment time of 90 s. Under optimal conditions, the linear range for acetaminophen is 2 × 10⁻⁶. -7Up to 2×10 -4 mol L -1 The detection limit is 5×10 -8 mol L -1 Compared with other sensors, this sensor exhibits better electrochemical parameters. Furthermore, the sensor constructed in this study can be used for the analysis and determination of acetaminophen in actual samples. This research provides a theoretical basis for ensuring that the content of acetaminophen in drugs and humans remains within safe limits.
Claims
1. A method for preparing an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, characterized in that, include: S10. Mix and grind the nano-graphite powder, glassy carbon microspheres, amino-functionalized ionic liquid and paraffin oil thoroughly to obtain a paste. S20. Fill the container with the paste and shape it to obtain an electrode post; S30. Polish the surface of the electrode post to obtain an amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen. The amino-functionalized ionic liquid is 1-aminopropyl-3-methylimidazolium hexafluorophosphate ionic liquid; The mass ratio of the nano-graphite powder to the amino-functionalized ionic liquid is 3:1.
5. The content of the glassy carbon microspheres is 40 wt%.
2. The method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen as described in claim 1, characterized in that, The volume ratio of the amino-functionalized ionic liquid to the paraffin oil is 1:
1.
3. The method for preparing the amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen as described in claim 1, characterized in that, The mass ratio of the nano-graphite powder to the glassy carbon microspheres is 3:
2.
4. An amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen, characterized in that, The electrode was prepared using the method described in any one of claims 1-3 for detecting acetaminophen. The relative standard deviation of six parallel determinations of acetaminophen using the same amino-functionalized ionic liquid / glassy carbon microsphere composite electrode was 1.04%. The relative standard deviation of acetaminophen detection using six different amino-functionalized ionic liquid / glassy carbon microsphere composite electrodes was 2.89%.
5. An electrochemical sensor for detecting acetaminophen, characterized in that, The amino-functionalized ionic liquid / glassy carbon microsphere composite electrode for detecting acetaminophen as described in claim 4 was used as the working electrode.
6. A method for detecting acetaminophen, characterized in that, Includes the following steps: T10. Construct the electrochemical sensor for detecting acetaminophen as described in claim 5; T20. Construct an electrolyte system, which consists of the sample to be tested and PBS buffer solution; T30, Detect the concentration of acetaminophen.
7. The method for detecting acetaminophen as described in claim 6, characterized in that, The concentration of the PBS buffer solution is 0.1 mol / L, and the pH value is 5-7.
8. The method for detecting acetaminophen as described in claim 7, characterized in that, The detection of acetaminophen concentration includes the following steps: At room temperature, using the square wave voltammetry method, enrichment was achieved at open circuit potential for 60 s–150 s.
Citation Information
Patent Citations
Carbon nanotube modified electrode for acetaminophen detection and preparation method of carbon nanotube modified electrode
CN111505074A
Ionic liquid functional composite membrane modified electrode and preparation method and application thereof to detection of chlorophenol
CN106018519A